Identification of cryptic coinfection with Plasmodium falciparum in patients presenting with vivax malaria. - Mayxay, M; Pukritrayakamee, S; Chotivanich, K; Imwong, M; Looareesuwan, S; White, N (2001)
In Thailand, approximately 8% of patients treated for vivax malaria are found subsequently to have coinfection with Plasmodium falciparum. A P. falciparum histidine rich protein 2 (PfHRP-2) dipstick test was evaluated as a predictor of mixed infections with subpatent P. falciparum in a prospective study of 238 patients admitted to the hospital with acute vivax malaria. Of these, 23 (10%) had subsequent development of falciparum malaria without reexposure. Patients with cryptic P. falciparum infection had a significantly lower mean (standard deviation) hematocrit than those with P. vivax alone: 29.6 (7.6%) versus 37.2 (6.4%) (P < 0.0001). Using microscopic appearance of P. falciparum after the start of treatment as the reference standard, the PfHRP-2 test was 74% sensitive and 99% specific in predicting mixed infections with subpatent P. falciparum parasitemia at presentation. The PfHRP-2 dipstick test may be a useful adjunct to microscopy in areas where mixed infections are common.